Fresno County Bar Association Law Day Luncheon: Attorney General John Van de Kamp - Watkins, Howard::::::::: (1987)
Sandra Snyder, John Van de Kamp, Samuel Palmer III and Fresno County Bar Association President Howard Watkins seated at head table